MANAGEMENT OF BUSINESS STRATEGY COMPANIES - Lyubov' P. Petrova; Yuliya Yu. Finogenova (Вестник Российского экономического университета имени Г. В. Плеханова)
In order to make internet trade successful it is necessary to analyze different economic indicators, take into account changing requirements of the market, take steps aimed at increasing profit, minimization of costs and use integrated assessment of the quality of company business strategy. The article deals with business strategy of selling goods in a Russian internet shop. The strategy was designed with regard to different marketing concepts by using various tools. The authors offer a short-term forecast of daily sales on the basis of autoregressive model. Interconnection between key approaches to adopt strategy variations was identified.